2014
DOI: 10.1002/cncr.29131
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐methods examination of communication between oncologists and primary care providers among primary care physicians in underserved communities

Abstract: Background Research has demonstrated that communication and care coordination improve cancer patient outcomes. To improve communication and care coordination, it is important to understand Primary Care Providers’ (PCPs’) perceptions of communication with oncologists as well as PCPs’ communication needs. Methods A mixed methods approach was utilized in the present study. In the qualitative phase of the study, 18 PCPs practicing in underserved, minority communities were interviewed about their experiences comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…For example, establishing formalized, explicit policies around triaging high-risk patients for a timely colonoscopy and for chemotherapy infusions and communicating these to all members of the MTS can help in reducing diagnostic and treatment delays. 36,37 …”
Section: Understanding the Multi-team System Through The Casementioning
confidence: 99%
“…For example, establishing formalized, explicit policies around triaging high-risk patients for a timely colonoscopy and for chemotherapy infusions and communicating these to all members of the MTS can help in reducing diagnostic and treatment delays. 36,37 …”
Section: Understanding the Multi-team System Through The Casementioning
confidence: 99%
“…The results of the questions on post-referral communication have been published elsewhere. 47 For this study, we developed two scale variables about cancer clinical trials. The first measured the physician’s attitudes and beliefs about trials by asking their level of agreement on a 5-point scale (1 Strongly Agree to 5 Strongly Disagree ) for six statements about clinical trials (as shown in Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This has been shown to be the case across different health care systems, such as in the US (Gandhi et al, 2000;Shen et al, 2015), Australia (Jefford et al, 2008;Lizama et al, 2015) and UK (Farquhar et al, 2005). This has been shown to be the case across different health care systems, such as in the US (Gandhi et al, 2000;Shen et al, 2015), Australia (Jefford et al, 2008;Lizama et al, 2015) and UK (Farquhar et al, 2005).…”
Section: Introductionmentioning
confidence: 91%